2022
DOI: 10.5194/bg-19-2741-2022
|View full text |Cite
|
Sign up to set email alerts
|

Modeling interactions between tides, storm surges, and river discharges in the Kapuas River delta

Abstract: Abstract. The Kapuas River delta is a unique estuary system on the western coast of the island of Borneo, Indonesia. Its hydrodynamics are driven by an interplay between storm surges, tides, and river discharges. These interactions are likely to be exacerbated by global warming, leading to more frequent compound flooding in the area. The mechanisms driving compound flooding events in the Kapuas River delta remain, however, poorly known. Here we attempt to fill this gap by assessing the interactions between riv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…Pontianak is one of the cities in West Kalimantan Province, Indonesia which is often affected by tidal floods, especially in the riverbank areas (BPIW, 2017;Gultom et al, 2020). Previous studies (Kuntinah et al, 2021;Sampurno et al, 2022a;Sampurno et al, 2022b) have shown that tidal flood in Pontianak often occurs during the high tide seasons from December to February. During this period, the tides reach a maximum height because affected by Asian monsoon (Kästner et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Pontianak is one of the cities in West Kalimantan Province, Indonesia which is often affected by tidal floods, especially in the riverbank areas (BPIW, 2017;Gultom et al, 2020). Previous studies (Kuntinah et al, 2021;Sampurno et al, 2022a;Sampurno et al, 2022b) have shown that tidal flood in Pontianak often occurs during the high tide seasons from December to February. During this period, the tides reach a maximum height because affected by Asian monsoon (Kästner et al, 2018).…”
Section: Introductionmentioning
confidence: 95%
“…According to Sampurno et al (2022a), the flood hazard along the Kapuas River is delineated into three regions. From the river mouth to 30 km upstream of the river (Pontianak) is the tidedominated area, where discharge no longer controls the maximum water level, which is correlated to flood hazards.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The water levels within the low-lying KRD are influenced by tide and wind surges from Karimata Strait, as well as the river discharges from the Kapuas and the Landak rivers (Sampurno et al 2022). The flood risk here, and in other deltas, are likely to increase in future climate (Kundzewicz et al 2014).…”
Section: Introductionmentioning
confidence: 99%